James Joyce Ulysses - Sherry, Vincent B. (Cambridge, U.K. ; New York : Cambridge University Press, 2004)
In this engaging introduction, Vincent Sherry combines a close reading of Ulysses with new critical arguments.
1. Introduction -- 1. Landmark: the ruined monument -- 2. Ireland and Europe: from the 1890s to the 1920s -- 3. Novel voices -- 2. Epic subjects -- 4. Telemachia -- 5. The odyssey -- 6. Nostos -- 7. "Wandering Rocks" and the art of gratuity -- 3. Lapsarian languages -- 8. Stephen Zero -- 9. Word incarnate, word carnival -- 10. Graphic lies -- P(ost) S(criptum) U(lysses) -- App. the schema.
Previous edition: 1994.
Includes bibliographical references (pages 117-125).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Joyce, James, -- 1882-1941.; Homer -- Influence; Bloom, Leopold -- (Fictitious character); Bloom, Molly -- (Fictitious character); Joyce, James, -- 1882-1941; Homère -- Influence; Homer; Ulysses (Joyce, James); Bloom, Leopold -- (Fictitious character); Bloom, Molly -- (Fictitious character); English fiction -- Greek influences; Dublin (Ireland) -- In literature; Bloom, Leopold (Personnage fictif); Bloom, Molly (Personnage fictif); Roman anglais -- Influence grecque; Dublin (Irlande) dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English fiction -- Greek influences; Influence (Literary, artistic, etc.); Literature; Ireland -- Dublin; Ulysses (Joyce); Electronic book